The effectiveness of the School Based-Cooperative Problem Based Learning (SB-CPBL) model in improving students' achievement in Science - Wael Musalamani,; Ruhizan Mohammad Yasin,; Kamisah Osman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
School Based-Cooperative Problem-Based Learning (SB-CPBL) model is a model that integrates Problem-Based Learning and Cooperative Learning towards becoming more student-centered. This study elucidates the effectiveness of the SB-CPBL model on 8th-grade students' achievement in science. The study was conducted in King Abdullah II School for Excellence in Jordan using four classes, assigned as experimental and control groups. The quasi-experimental with non-equivalent control group pre-test/post-test design was used, with a sample of 120 students from both genders. Two classes (60 students) were selected randomly as an experimental group learning via the SB-CPBL Module, while the other two classes (60 students) that assigned as the control group followed their teacher’s usual approach of teaching. A treatment period of 6 weeks was used in this research. A science achievement test was employed to measure the differences in the dependent variable quantitatively. Data analyses confirmed that the SB-CPBL students had higher scores in the achievement post-test relative to their counterparts in the traditional group. Also, the results showed that the difference between the SB-CPBL module and traditional teaching methods is not dependent on the achievement levels of the students. The analysis showed significant main effects of gender in the context of achievement. The findings implicate that SB-CPBL can help in providing meaningful science education that meets the needs of the students in the 21st century.